A bioassay for the detection of benzimidazoles reveals their presence in a range of environmental samples - Crofts, Terence S.; Men, Yujie; Alvarez-Cohen, Lisa; Taga, Michiko E. (Frontiers in Microbiology, 2014)
Cobamides are a family of enzyme cofactors that include vitamin B12 (cobalamin) and are produced solely by prokaryotes. Structural variability in the lower axial ligand has been observed in cobamides produced by diverse organisms. Of the three classes of lower ligands, the benzimidazoles are uniquely found in cobamides, whereas the purine and phenolic bases have additional biological functions. Many organisms acquire cobamides by salvaging and remodeling cobamides or their precursors from the environment. These processes require free benzimidazoles for incorporation as lower ligands, though the presence of benzimidazoles in the environment has not been previously investigated. Here, we report a new purification method and bioassay to measure the total free benzimidazole content of samples from microbial communities and laboratory media components. The bioassay relies on the “calcofluor-bright” phenotype of a bluB mutant of the model cobalamin-producing bacterium Sinorhizobium meliloti. The concentrations of individual benzimidazoles in these samples were measured by liquid chromatography-tandem mass spectrometry. Several benzimidazoles were detected in subpicomolar to subnanomolar concentrations in host-associated and environmental samples. In addition, benzimidazoles were found to be common contaminants of laboratory media components. These results suggest that benzimidazoles present in the environment and in laboratory media have the potential to influence microbial metabolic activities.